Hepatitis E Virus Detection in Liver Tissue from Patients with Suspected Drug-Induced Liver Injury - Chijioke, Obinna; Bawohl, Marion; Springer, Erik; Weber, Achim (Frontiers in Medicine, 2015)
Hepatitis E virus (HEV) infection is increasingly recognized as a cause of acute hepatitis in the industrialized world. We aimed to determine the frequency of acute Hepatitis E virus (HEV) infection in cases of suspected drug-induced liver injury (DILI), mainly a diagnosis of exclusion. To this aim, formalin-fixed, paraffin-embedded (FFPE) liver tissues of all cases routinely processed in our institute during a 2 ½ years period in which DILI was amongst the differential diagnoses (157 liver biopsies, one liver explant) were subjected to semi-nested RT-PCR for the detection of hepatitis E virus (HEV) RNA. Histopathology was re-evaluated on all cases tested positive. HEV RNA was detectable in three of 158 cases (2%) tested, comprising autochthonic as well as travel-related infections with genotypes 1, 3, and 4 each found once, respectively. Histopathologic findings comprised one case with subtotal hepatic necrosis and two cases of acute (cholestatic) hepatitis not distinguishable from acute hepatitis of other etiology. Thus, the overall frequency of acute hepatitis E virus (HEV) infection as determined by detection of hepatitis E virus (HEV) RNA in liver tissue is substantially increased in patients with suspected drug-induced liver injury compared to the healthy population, emphasizing the need to actively look for hepatitis E virus (HEV) infection in cases of suspected drug-induced liver injury (DILI). Molecular testing for hepatitis E virus (HEV) RNA in routinely processed formalin-fixed, paraffin-embedded (FFPE) liver tissues can be applied to cases with undetermined hepatitis E virus (HEV) status.